Optimization and Partial Characterization of a Putative Probiotic Bacterium Antagonistic to Vibrios in Shrimp Larval Rearing System - Sarker, Abdullah; Rahman, Shafiqur; Khan, Shakila N; Naser, M Niamul (Dhaka University Journal of Pharmaceutical Sciences, 2011)
Organic aquaculture utilizing probiotics for disease control and bioremediation has gained global acceptance in recent years. A preliminary study was conducted to isolate indigenous bacteria antagonistic to pathogenic vibrios as putative probiotics for shrimp hatcheries and grow-out systems. These efforts resulted in the isolation of a Gram-positive bacilli after screening thirty one water samples, collected from the coastal areas of the Bay of Bengal. This probiont, identified as Bacillus licheniformis exhibited vibriocidal activity in vitro against 60% of the Vibrio species isolated from the same water samples based on broad spectrum antagonistic and hydrolytic properties. In this study, we looked into the effects of pH, temperature, salinity, surfactants (Triton X114, Tween 80 and SDS) and EDTA on the vibriocidal property of the cell-free supernatant of the probiotic and observed that the antagonistic property was refractory to the surfactants used. The optimum activity of the cell-free supernatant was observed at 30°C, below and above which there was a marked decline in the inhibition. Neutral and alkaline pH ranges favored the antagonistic property while it was negligible at acidic ranges. The metal chelator EDTA nullified the antagonistic property at 0.01 mM concentration, the lowest tested, indicating the presence of a metal active group in the active fraction. The study suggests the potential of the selected bacterial isolate as a putative, antagonistic probiotic useful in the aquaculture systems of the tropics considering its broad antagonistic activity, higher activity in the neutral and alkaline pH and optimum activity at 30°C. Efforts are underway to purify and characterize the antagonistic compound in the cell-free supernatant. Key words: Probiotic; vibrios; Bacillus; shrimp; cell-free supernatant DOI: 10.3329/dujps.v9i1.7426 Dhaka Univ. J. Pharm. Sci. 9(1): 23-29 2010 (June)